Implementasi Kegiatan Cotton Bud Painting Untuk Mengembangkan Kemampuan Motorik Halus Anak Usia 4-5 Tahun Di Ra Tarbiyatul Ula - Imas Datul Mukhriyah; Umi Masturoh (Program Studi Pendidikan Islam Anak Usia Dini, 2022)
Cotton Bud Painting is a painting activity using cotton buds or media that can train children's fine motor development aspects, stimulate children's cognitive and social emotional development. This study aims to develop fine motor skills of children aged 4-5 years through cotton bud painting activities. The focus of the problems in this study are: 1) How is the implementation of cotton bud painting activities to develop fine motor skills of children aged 4-5 years?2) What are the supporting and inhibiting factors for implementing cotton bud painting activities to develop fine motor skills of children aged 4-5 years? This study uses descriptive qualitative research methods. Data collection techniques used are interviews, observation, and documentation. The results showed that: 1) The implementation of cotton bud painting activities was able to develop children's fine motor skills as seen from the observations that children were able to hold cotton buds correctly, placing the right colors in their paintings. 2) The supporting factor in this study is the role of parents who always support activities at school. While the inhibiting factor is the child's lack of interest in participating in learning because learning is always carried out indoors